2014
DOI: 10.1371/journal.pone.0108428
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Is Essential for High Temperature Tolerance in Invasive Bemisia tabaci Middle East Asia Minor 1 Cryptic Species

Abstract: Temperature is an important factor in affecting population dynamics and diffusion distribution of organisms. Alien species can successfully invade and colonize to various temperature environments, and one of important reasons is that alien species have a strong resistance to stress temperature. Recently, researchers have focused on the mechanisms of temperature sensing to determine the sensing and regulation mechanisms of temperature adaptation. The transient receptor potential (TRP) is one of the key componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…B . tabaci has emerged as a promising model to understand the molecular basis of abiotic stress tolerance and adaptation for invasion biology [ 34 37 ]. As an invasive species, thermotolerance represent crucial mechanism for MED to successfully colonize new habitats [ 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…B . tabaci has emerged as a promising model to understand the molecular basis of abiotic stress tolerance and adaptation for invasion biology [ 34 37 ]. As an invasive species, thermotolerance represent crucial mechanism for MED to successfully colonize new habitats [ 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was believed that the TRP channel usually contains four subunits, each of which has six transmembrane proteins, and its N-terminal and C-terminal are both intracellular [58], which is consistent with the protein prediction results of the TaPyx protein. However, studies in invertebrates have also found that the N-terminal and C-terminal of the TRP channel exist extracellular, such as the TRP channel in B. tabaci [51]. In fact, TRP is a class of nonselective cationic channel proteins that exist on the membrane of the cell membrane or intracellular organelle membrane, and the mechanism of its signal conversion in many systems needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of two cryptic species of Bemisia tabaci AsiaII3 and MEAM1 (Middle East Asia Minor 1), it was found that temperature stress could induce the expression of BtTRP mRNA, and played an important role in heat tolerance. According to this characteristic, researchers infer that BtTRP also belongs to the TRPA subfamily [51][52][53]. Therefore, the TRPA subfamily plays an important role in temperature sensing and the heat escape injury response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure of invasive whiteflies to thermal stress is accompanied by rapid alterations in their gene expression ( Lü and Wan, 2008 ; Mahadav et al, 2009 ; Lü et al, 2014a ; Dai et al, 2018a ). Lü et al (2014b) conducted heat shock experiments with MED and found that its survival rate was significantly improved within two generations.…”
Section: Introductionmentioning
confidence: 99%